Implementasi Pendampingan Remaja Berbasis Alkitabiah untuk Penguatan Karakter Kristiani di Gereja Lokal - Fanni Boen; Satya Ywana; Victor Deak (Journal of Community Development, 2026)
Youth mentoring programs represent an important strategy in church ministry to strengthen Christian character among adolescents who face various moral, social, and spiritual challenges in the modern era. However, many churches still lack structured mentoring models that are grounded in biblical values and implemented in a systematic manner. This community service program aims to implement a biblical-based youth mentoring model as an effort to strengthen Christian character and spiritual maturity among adolescents within the context of a local church. The program was conducted through several mentoring activities, including small group spiritual guidance, Bible reflection sessions, interactive discussions, and active involvement of youth in church ministry activities. The implementation involved youth mentors, church leaders, and adolescent participants who took part in the mentoring activities in a participatory manner. The results indicate that a relational and dialogical mentoring approach grounded in biblical values can increase youth participation in church activities, strengthen their faith identity, and foster the development of Christian character such as responsibility, leadership, and spiritual commitment. In addition, the program helps the church develop a more structured and contextual approach to youth spiritual formation. Therefore, a biblical-based youth mentoring model can serve as a strategic approach for churches in nurturing a generation of young believers who reflect Christlike character and contribute positively to the life of the church and society.